Adaptive Video Streaming Through Server Driven Rate Control In Manets (International Journal of Engineering and Computer Science, 2016)
The IEEE 802.11standard is developed and gained unprecedented popularity for its simple and cost-effective wireless technology to provide best effort services. But, it has to address serious challenges concerned to multimedia services. Quality of Service (QOS) is one of the most prominent among them. The tradeoff between the video quality and the streaming performance is eliminated by the quality driven rate controller’s. They treat all the users alike but, where in practical it cannot be. The educational videos must be of more video quality than that of the video news, where video streaming must be more. To address the problem the proposedEquity Enhanced Distributed Channel Access (EEDCA) prioritizes the traffic according to their type and also focus on providing the Quality of Service (QOS) of a Mobile Adhoc Network (MANET) to equally distribute the resources among all the nodes to gratify the users.